The Relationship between Power and Knowledge in Islamic Education: A Post-Colonial Discourse Analysis of Islamic Thought in Madura - Baitiyah; Nor Hasan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines the power-knowledge relationship in contemporary Islamic education discourse in Indonesia through the lens of postcolonial theory. Using the Fairclough model of Critical Discourse Analysis (CDA), this study analyzes three dimensions: text, discourse practice, and social practice. Data were collected through a document review of the official curriculum (KMA 183 of 2019) and the main textbook (Aqidah Akhlak, History of Islamic Culture), supplemented by semi-structured interviews with 15-20 policy makers, textbook writers, and education practitioners, as well as contextual observations. Intertextual and historical analysis was conducted to trace the continuity of colonial legacies. Triangulation of sources and theories as well as the critical reflectivity of the researcher is applied to ensure the credibility of the findings. The results of the study reveal an epistemological paradox in which Islamic education, while striving for autonomy, actually reproduces the logic of colonial power through the hierarchy of knowledge (naqli vs aqli), canonization of texts, and symptoms of internal orientalism. In response, this study contributes an Integrative-Decolonized Epistemology Model that offers transformation through canon deconstruction, dialectical integration, indigenization of local knowledge, and reflective-participatory pedagogy to shift Islamic education from a consumer to an autonomous and contextual producer of knowledge.